Genome-Wide Analysis and Characterization of SABATH Gene Family in Phaseolus vulgaris Genotypes Subject to Melatonin under Drought and Salinity Stresses - Aygören, Ahmed Sidar; Güneş, Ebru; Muslu, Selman; Kasapoğlu, Ayşe Gül; Yiğider, Esma; Aydın, Murat; Büyük, İlker; İlhan, Emre (Plant molecular biology reporter, 2023)
The SABATH gene family is a plant-specific class of small molecule methyltransferases. The first goal of this study was to conduct a genome-wide analysis and in silico characterization of SABATH gene family members in Phaseolus vulgaris . The second goal was to see how the members of the SABATH gene family react to salt and drought stress, as well as their expression patterns when melatonin is added to the mix. Within the scope of the study, 18 Pvul-SABATH proteins were discovered in the Phaseolus vulgaris genome using various in silico methods. These proteins ranged in size from 30.18 to 42.73 kDa and were made up of 268 to 387 amino acids. The Pvul-SABATH proteins had isoelectric points ranging from 4.95 (Pvul-SABATH-8) to 6.08 (Pvul-SABATH-2 and -3). The Pvul-SABATH genes were found to have at least three but no more than four exons. According to the results of the phylogenetic analysis, Pvul-SABATH proteins were found to be clustered in three major groups with Arabidopsis thaliana , Glycine max species, and various methyltransferase members. There was segmental duplication between the Pvul-SABATH-1 and Pvul-SABATH-5 genes, as well as the Pvul-SABATH-10 and Pvul-SABATH-14 genes. By comparing the expression level of Pvul-SABATH genes, their different expression levels depending on the bean cultivars were discovered. Moreover, these findings suggested that Pvul-SABATH genes may play a role in the growth and development process of the plants in response to various biotic and abiotic stresses. The findings of this study, which is the first to look at the SABATH gene family in Phaseolus vulgaris , are thought to be beneficial in plant biotechnology and molecular biology.